CAUSES OF VARIATIONS OF ND-O ISOTOPE RATIOS OF GRANITOIDS IN THE TUVA-MONGOLIA MICROCONTINENT AND ITS EARLY CALEDONIAN FRAMING - Krylov D.P.; Kozakov I.K.; Glebovitsky V.A.; Fedoseenko A.M. (My University, 2006)
Variations of neodymium and oxygen isotopic compositions of postcollision granitoids in the Tuva–Mongolia microcontinnet (TMM) is determined largely by different compositions of magma sources due to the mixing of two components. Component M is a juvenile mantle (N-MORB or similar source in isotopic composition) material (δ18O ~6‰ and 143Nd/144Nd ~ 0.51235). Component C corresponds to a material with a long crustal prehistory (δ18O ~12.0–12.5‰ and 143Nd/144Nd ~ 0.51186).